2015
DOI: 10.1371/journal.pbio.1002231
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical Rebound Depolarization Enhances Visual Perception

Abstract: Animals are constantly exposed to the time-varying visual world. Because visual perception is modulated by immediately prior visual experience, visual cortical neurons may register recent visual history into a specific form of offline activity and link it to later visual input. To examine how preceding visual inputs interact with upcoming information at the single neuron level, we designed a simple stimulation protocol in which a brief, orientated flashing stimulus was subsequently coupled to visual stimuli wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 83 publications
20
38
0
Order By: Relevance
“…Flashing stimuli compared to drifting sinusoidal gratings or reversal checkerboards are rather strong stimuli, thus can evoke changes faster. It was shown before that in adult mice flashing stimuli robustly evoke long-term changes in the V1 neuronal response and increase the broadband power of LFP signal [30,31]. Thus, the flash stimulus might be successfully used for the induction of modulation in the neuronal response [32], which we confirmed in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Flashing stimuli compared to drifting sinusoidal gratings or reversal checkerboards are rather strong stimuli, thus can evoke changes faster. It was shown before that in adult mice flashing stimuli robustly evoke long-term changes in the V1 neuronal response and increase the broadband power of LFP signal [30,31]. Thus, the flash stimulus might be successfully used for the induction of modulation in the neuronal response [32], which we confirmed in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have shown that brief stimulus presentations at high contrast produce strong persistent activity in primary visual cortex (Funayama et al, 2015;Huang et al, 2008). In our data, the flashed visual stimulus evoked a biphasic population response (example in Figure 1A), with an initial transient component which started immediately after stimulus onset and a delayed reverberatory component which started ~200 ms after stimulus offset.…”
Section: Resultssupporting
confidence: 71%
“…Yet, stimulus-evoked responses in the primary visual cortex propagate through the local circuitry in wave-like patterns (Benucci et al, 2007;Xu et al, 2007, Grinvald Arieli and Janke) and can persist long after the cessation of stimulation (Benucci et al, 2009;Funayama et al, 2015;Huang et al, 2008;Nikolić et al, 2009). These complex and temporally-extended population responses have been implicated in reward timing (Chubykin et al, 2013;Gavornik et al, 2009;Shuler and Bear, 2006), working memory (Harrison and Tong, 2009;Munneke et al, 2010;Supèr et al, 2001) and are known to interact with (Benucci et al, 2009;Funayama et al, 2015;Gavornik and Bear, 2014;Nikolić et al, 2009;Wolff et al, 2017) and modulate the perception of (Brascamp et al, 2007;Fischer and Whitney, 2014;Funayama et al, 2015;Huang et al, 2008;Kahneman et al, 1992) subsequent visual stimulation. These dynamic properties exhibited by early visual neurons together with the exposure-dependent changes of stimulusresponses, suggest a direct involvement of primary visual cortex in the active distributed representation of more complex visual features, thus supporting a more constructive interpretation of primary cortex function (Olshausen and Field, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5A). At lower frequencies (< 4 Hz), complex biphasic responses were common in S1 and V1, as has been previously reported in rodents and humans (Funayama et al, 2016;Funayama et al 2015;Sachidhanandam et al, 2013). We found, however that these multiphasic responses shifted to simple, monophasic responses as stimulus frequency increased to 4 Hz.…”
Section: Change In Response Complexity With Stimulus Frequencysupporting
confidence: 85%